Comparison of cardiovascular outcomes and cardiometabolic risk factors between patients with type 2 diabetes treated with sodium-glucose cotransporter-2 inhibitors and dipeptidyl peptidase-4 inhibitors: a meta-analysis. (17th June 2021) - Wang, Siwen; Wu, Ting; Zuo, Zhihong; Jin, Ping; Luo, Xuan; Deng, Meichun
Abstract: Aims : Prevention of cardiovascular outcomes is a goal of the management of patients with type 2 diabetes mellitus patients as important as lowering blood glucose levels. Among the various glucose-lowering agents, the effects of sodium-glucose cotransporter-2 inhibitors (SGLT-2Is) and dipeptidyl peptidase-4 inhibitors (DPP-4Is) on cardiovascular outcomes have become the focus of recent researches. Methods and results : A systematic search was performed through several online database. All studies that compared the effects of SGLT-2Is and DPP-4Is on cardiovascular outcomes and cardiometabolic risk factors were reviewed. A total of 30 studies were included. Compared with DPP-4Is, SGLT-2Is treatment reduced the risk of stroke [risk ratio (RR) = 0.80; 95% confidence interval (CI), 0.76–0.84], myocardial infarction (RR = 0.85; 95% CI, 0.81–0.89), heart failure (RR = 0.58; 95% CI, 0.54–0.62), cardiovascular mortality (RR = 0.55; 95% CI, 0.51–0.60), and all-cause mortality (RR = 0.60; 95% CI, 0.57–0.63). In addition, SGLT-2Is presented favourable effects on hemoglobinA1c, fasting plasma glucose, systolic blood pressure, and diastolic blood pressure. The differences in blood lipids were also compared. Conclusion: Sodium-glucose cotransporter-2 inhibitors are superior to DPP-4Is in terms of cardiovascular outcomes. Sodium-glucose cotransporter-2 inhibitors bring more benefits with respect to the cardiometabolic risk factors.